Spontaneous mesenteric hematoma after antiplatelet therapy: a case report - Liang, Chen; Takahashi, Kazuhiro; Furuya, Kinji; Sakashita, Mai; Sakashita, Shingo; Noguchi, Masayuki; Nobuhiro, Nobuhiro (International Surgery Journal, 2018)
Spontaneous mesenteric hematoma (SMH) is one of the rare conditions with abdominal mass secondary to hemorrhage. It develops due to regional bleeding in the mesenteric vessel of a gastrointestinal tract. The unusual morphology and lack of apparent etiology of SMH make it difficult to diagnose. A 57-year-old woman was referred to our hospital for intermittent abdominal pain with nausea and vomiting. She was receiving antiplatelet therapy by aspirin from idiopathic thrombocytosis. The number of platelet was above the normal level. CT showed a tumor-like lesion with arterial extravasation in the left lower abdomen. Mesenteric hematoma was considered since the mass was located between two branches of inferior sigmoid artery (IMA). Emergency laparotomy was performed and a mesenteric hematoma adjacent to the sigmoid colon was identified. The mesenteric hematoma was resected with the regional sigmoid colon. Pathology report showed intact mucous membrane of the excision without tumors or aneurysm. SMH was finally confirmed. The patient returned to her daily life without complaining of any symptoms. When a patient on antiplatelet therapy complained of acute abdominal pain, SMH has to be taken into consideration. Abdominopelvic CT scan is an effective investigation for diagnosis, and conservative therapy or emergent exploratory laparotomy could be an optional treatment. To the best of our research in Medline, there have only seven cases of colorectal SMH. Authors reportrd a rare case of SMH located at sigmoid colon, which appeared after antiplatelet therapy.